Analysis of salivary flow, buffering capacity, and biochemical parameters in patients with chronic apical abscess - Moraes, Yuri Gabriel Chamorro de [UNESP] (Universidade Estadual Paulista (Unesp), 2026)
This study aimed to evaluate salivary flow rate and a panel of salivary biomarkers in patients with chronic apical abscess (CAA). Twenty-six systemically healthy individuals were allocated into two groups: Control (healthy, asymptomatic individuals with a disease-free oral cavity; n = 13) and CAA (patients with chronic apical abscess; n = 13). The CAA group was evaluated at baseline and at follow-up, one month after endodontic treatment and resolution of clinical signs, characterizing a partially longitudinal design. Unstimulated whole saliva was collected by the spitting method. Salivary flow rate, pH, buffering capacity, amylase, total protein, calcium, phosphate, chloride, lipid peroxidation, protein carbonyl content, nitrite, total oxidant capacity (TOC), total antioxidant capacity (TAC), uric acid, phosphatases, and transaminases were analyzed. At baseline, CAA patients showed higher salivary pH, calcium, and nitrite, along with reduced TAC and uric acid, compared with controls. At follow-up, patients exhibited increased salivary flow rate and TAC, together with reduced tartrate-resistant acid phosphatase, chloride, and lipid peroxidation, compared with baseline. This exploratory study indicates that saliva may serve as a useful source of biological information in endodontic infections. Alterations in salivary redox parameters support their potential relevance as adjunct markers of disease activity and treatment-related changes in CAA. Further well-powered longitudinal studies are required to validate these findings and clarify their clinical significance.

Este estudo teve como objetivo avaliar a taxa de fluxo salivar e um painel de biomarcadores salivares em pacientes com abscesso apical crônico (AAC). Vinte e seis indivíduos sistemicamente saudáveis foram alocados em dois grupos: Controle (indivíduos saudáveis, assintomáticos e com cavidade oral clinicamente livre de doença; n = 13) e AAC (pacientes com abscesso apical crônico; n = 13). O grupo AAC foi avaliado no baseline e no acompanhamento, um mês após o tratamento endodôntico e a resolução dos sinais clínicos, caracterizando um delineamento parcialmente longitudinal. A saliva total não estimulada foi coletada pelo método de cuspir. Foram analisados a taxa de fluxo salivar, pH, capacidade tamponante, amilase, proteína total, cálcio, fosfato, cloreto, peroxidação lipídica, conteúdo de carbonilas proteicas, nitrito, capacidade oxidante total (TOC), capacidade antioxidante total (TAC), ácido úrico, fosfatases e transaminases. No baseline, pacientes com AAC apresentaram valores mais elevados de pH salivar, cálcio e nitrito, juntamente com redução da TAC e do ácido úrico, em comparação ao grupo controle. No acompanhamento, os pacientes exibiram aumento da taxa de fluxo salivar e da TAC, além de redução da fosfatase ácida resistente ao tartarato, do cloreto e da peroxidação lipídica, em comparação ao baseline. Este estudo exploratório indica que a saliva pode servir como uma fonte útil de informações biológicas em infecções endodônticas. As alterações nos parâmetros redox salivares sustentam sua potencial relevância como marcadores adjuvantes da atividade da doença e das mudanças relacionadas ao tratamento no AAC. Estudos longitudinais futuros, com maior poder estatístico, são necessários para validar esses achados e esclarecer sua significância clínica.
Análise do fluxo, capacidade tamponante e parâmetros bioquímicos salivares em pacientes com abscesso apical crônico
Keywords: Abscesso periapical; Saliva; Estresse oxidativo; Bioquímica; Periapical abscess